Diario social di un Rettore 4 Conversazioni impossibili e dialoghi improbabili - Dei, Luigi (Libere carte, 2019)
Luigi Dei has found his own language through which he, while amusing himself and everyone else, offers us food for thought, information, knowledge and, above all, with continuity and originality, he disseminates science by apparently talking about other things, playing with our emotions, with our history, traditions and common sense. A cultural divertissement in which the author exploits the visibility and prestige of his role as Rector to give credibility and legitimacy to the project of making scientific knowledge more and more accessible and shared, also thanks to his great ability to intertwine themes and languages. Dei uses all the colours of the diversified palette of scientific disciplines constituting our knowledge in order to show us how each of them is assigned an irreplaceable role in that task of understanding reality that science has always taken on. He highlights how science combines method and rigour with creativity and imagination, but he also combines research and scientific knowledge with sensitivity and communication skills. (Laura Solito)